Management of nitrogen fertilization in maize cultivated in succession to black oats in a temperate climate - Ribeiro, Ricardo Henrique; Besen, Marcos Renan; Fioreze, Samuel Luiz; Piva, Jonatas Thiago (Comunicata Scientiae, 2018)
The objective of this study was to verify early nitrogen (N) fertilization on maize cultivated in succession to black oats. We conducted three experiments, relating to the 2012/13, 2013/14, and 2014/15 growing seasons, at UFSC-Curitibanos, in a randomized complete block experimental design, with four treatments and four replicates. The treatments were N management strategies in which the amount of N applied to maize was split into pre-sowing, at sowing, and topdressing times: (T1) control with no N application; (T2) 2/3 - 1/3 - 0; (T3) 1/3 - 1/3 - 1/3; and (T4) 0 - 1/3 - 2/3. The biometrics and productive potential parameters of the crop were evaluated. Application of N, regardless of the treatment, increased the yield. In 2012/13, there were no significant differences between the ways in which the N application was split, although they produced a higher yield than the control, resulting in a mean yield of 5,008 kg ha-1. In 2013/14, T2 was similar to T3 and T4, resulting in a yield of 9,858 kg ha-1; in 2014/15, T3 and T4 were similar, with a mean yield of 12,466 kg ha-1, while T2 resulted in a lower yield of 10,487 kg ha-1. When 2/3 of the N is applied pre-sowing, it is only effective when it is associated with the occurrence of a drought period at an early developmental stage of the plants. In adequate rainfall conditions, the early application of N fertilization is only effective when combined with a further 1/3 of the amount of N at sowing, and later as a topdressing.